Perioperative Care - Parrish II, Richard H.; Kortbeek, John (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Perioperative care practices worldwide are in the midst of a seeing change with the implementation of multidisciplinary processes that improve surgical outcomes through (1) better patient education, engagement, and participation; (2) enhanced pre-operative, intra-operative, and post-operative care bundles; and (3) interactive audit programs that provide feedback to the surgical team. These improved outcomes include reductions in the frequency and severity of complications and improved throughput, which ultimately reduce operative stress. Practices in theatre as well as ward are becoming more collaborative and evidence-driven.This book is best utilized by perioperative care team members engaged in quality improvement, collaborative practice, and application of innovations in surgical care.